University of the Philippines Diliman, Institute of Library and Information Science Library proposed collection development program - Sampang, Rizchelle F. (Institute of Library and Information Science, University of the Philippines Diliman, 2005)
This study aimed to draft a collection development program for the University of the Philippines, Institute of Library and Information Science (UP ILIS). User-study and collection evaluation were conducted and the theses of Methyl A. Raca (2000) and Ruel Montes Nandwani (1998) were adopted.